Evolution of theological views on evolution - Halaczek, Bernard (Anthropological Review, 1997)
Biology-oriented theology and philosophy-oriented biology have been a matter of controversy in the studies of human origins. This controversy terminates at the point when they both recognise their peculiarity: biology is concerned with the “how” man came into existence and theology with “what” of the existence of man.